Prophetic Communication of Islamic and Christian Religious Leaders in Overcoming Conflict of Religious Harmony (Social Studies at Griya 1, Martubung Village, Medan City) - Fauzan Hazim Tanjung; Ali Akbar (UNIVERSITAS PAKUAN, 2023)
This essay investigates the religious leaders' employment of prophetic communication. In modern-day Indonesia, disregard for ethics is an evident concern, giving rise to strong subjectivity and ethnocentrism. The emergence of this issue made it difficult for religious leaders to resolve societal difficulties. Personal interest in preaching is a problem that must be set aside if a moderate society is to be established. This study employs a qualitative, phenomenological methodology. The writers obtain their data through interviews, observations, and documentation. The primary informants for this study were religious leaders at the research site, while the community comprised the secondary informants. The findings indicate that ethical negligence persists and is defined by a number of contemporary events. The Qur'an describes six prophetic communications of the Apostles as a guideline for preaching in order to mitigate this issue. These six principles then serve as the foundation for religious leaders' sermons, allowing them to foster a reasonable attitude in society.